LAPORAN KEUANGAN KONSOLIDASI SEKTOR PUBLIK (Perbandingan Beberapa Negara) - Wiwin Kurniasari (Jurnal Akuntansi, 2013)
The consolidated Financial Report (CFR) in the public sector takes on considerable contribute to carrying out public policies. The accounting system must represent this overall scenario and analyzes eight countries (Indonesian, Australia, New Zeland, Canada, Sweden, France, USA, and the U.K.), as well as the new informational requirements of the International Public Sector Accounting Standards (IPSASs). Accounting prinsiples used for compling a CFR in the public sector will be compared. The objective of the study is highligt the similiarities and differeces between the various prinsiples and consideration of related to the consolidation of annual accounts in the public sector. Keywords: Consolidated Financial Report, Public Sector, International Accounting Principles, Accountability.